Novel antibiotics against Staphylococcus aureus without detectable resistance by targeting proton motive force and FtsH - She Pengfei; Yang Yifan; Li Linhui; Li Yimin; Xiao Dan; Guo Shaowei; Huang Guanqing; Wu Yong (MedComm)
Abstract The increased prevalence of methicillin‐resistant Staphylococcus aureus (MRSA) and its biofilms poses a great threat to human health. Especially, S. aureus‐related osteomyelitis was hardly cured even by conventional antibiotics combined with surgical treatment. The development of novel structural antibiotics is urgently needed. By high‐throughput screening and rational design, we identified a small molecule C218‐0546 and its optimized analog STK848198 with great antimicrobial potential against MRSA avoiding resistance occurrence. And significant synergistical antimicrobial effects were found between the molecules and conventional antibiotics. Mechanisms studies by transcriptomics, fluorescent probes, molecule dynamics, and plasma surface resonance indicated that the proton motive force as well as FtsH are the main potential targets of these molecules. The compounds exhibited excellent in vivo pharmacokinetics, toxicity profiles, and antimicrobial activities in the abscess model as well as the peritonitis‐sepsis model. In addition, STK848198 was found to be effective against MRSA biofilms by interacting with the quorum sensing system. STK848198 also showed in vivo efficacy in the periprosthetic joint infection model. In all, our study identified a class of antimicrobials with novel scaffolds that could be potential alternatives for the treatment of MRSA and its biofilm‐related infections.